2018
DOI: 10.1016/j.ymthe.2018.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Species-Specific Involvement of Integrin αIIbβ3 in a Monoclonal Antibody CH12 Triggers Off-Target Thrombocytopenia in Cynomolgus Monkeys

Abstract: CH12 is a novel humanized monoclonal antibody against epidermal growth factor receptor variant III (EGFRvIII) for cancer treatment. Unfortunately, in pre-clinical safety evaluation studies, acute thrombocytopenia was observed after administration of CH12 in cynomolgus monkeys, but not rats. More importantly, in vitro experiments found that CH12 can bind and activate platelets in cynomolgus monkey, but not human peripheral blood samples. Cynomolgus monkey-specific thrombocytopenia has been reported previously; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The anti-PD1 antibody SHR-1210 (camrelizumab) exhibits potent PD1 antagonism in man, but uniquely among PD(L)1 pathway drugs, it causes capillary hemangioma in most patients dosed. 31 , 35 , 36 Hemangioma is a benign tumor in which blood vessels hyper-proliferate in the skin and potentially in the liver and other organs. 37 In a recent study, proteomic screening using a cell microarray library of >5,500 human proteins successfully identified that SHR-1210 binds not only human and monkey PD1, but also human vascular endothelial growth factor receptor 2 (VEGFR2), FZD5 and ULBP2.…”
Section: Introductionmentioning
confidence: 99%
“…The anti-PD1 antibody SHR-1210 (camrelizumab) exhibits potent PD1 antagonism in man, but uniquely among PD(L)1 pathway drugs, it causes capillary hemangioma in most patients dosed. 31 , 35 , 36 Hemangioma is a benign tumor in which blood vessels hyper-proliferate in the skin and potentially in the liver and other organs. 37 In a recent study, proteomic screening using a cell microarray library of >5,500 human proteins successfully identified that SHR-1210 binds not only human and monkey PD1, but also human vascular endothelial growth factor receptor 2 (VEGFR2), FZD5 and ULBP2.…”
Section: Introductionmentioning
confidence: 99%
“…43 Off-target platelet binding and activation due to the overloading of the therapeutic drug in blood can result in platelet acti-vation and eventually destruction. 44 The immune system can also play a major role in platelet destruction by inducing antiplatelet antibodies against the murine sequences of the chimeric Fab molecule. 31 ii.…”
Section: Drug-induced Thrombocytopenia (Dit)mentioning
confidence: 99%
“…Bevacizumab 49 Platelet consumption due to endothelial dysfunction from lack of VEGF Anti-CD40L mAbs 50 Inhibits disaggregation of ADP-aggregated platelets Abciximab 51 Induction of antiplatelet antibodies directed against the murine sequences of chimeric Fab molecule TNF-α inhibitors 52,53 Induces autoantibodies including antiplatelet antibodies or suppression of hematopoiesis AMG X and LY2541546 54,55 Platelet activation by direct binding to platelets and/ or megakaryocytes causes the release of serotonin Thrombopoietic agents-rHu-TPO or PEG-rHuMGDF 43 Cross-Reacts with endogenous thrombopoietin and neutralizes CH12 humAb 44 Off-target platelet binding and activation resulting in platelet destruction…”
Section: Bone Marrow Toxicity and Inhibits Megakaryocyte Differentiat...mentioning
confidence: 99%
“…[53][54][55] Integrin not only mediates the adhesion of HCC cells to other HCC cells and HCC cells to the ECM but also participates in the chemotaxis, proliferation, and apoptosis of tumor cells, and thus, integrin involvement extends nearly throughout the entire process of HCC cell invasion and metastasis. [56][57][58][59][60] The monoclonal antibodies LM609 and Vitaxin of integrin aVb3 also showed good antiangiogenic effects in vitro and in vivo, and Vitaxin has subsequently entered phase II clinical trials. 61 Matrix metalloproteinase is a type of proteolytic enzyme involved in the degradation of the ECM and basement membrane.…”
Section: Matrix Metalloproteinase Inhibitorsmentioning
confidence: 99%